A Novel Penning‐Trap Design for the High‐Precision Measurement of the 3He2 + Nuclear Magnetic Moment. Issue 5 (2nd April 2019) - Schneider, Antonia; Mooser, Andreas; Rischka, Alexander; Blaum, Klaus; Ulmer, Stefan; Walz, Jochen
Abstract: A new experiment is constructed aiming at the first direct high‐precision measurement of the helium‐3 nuclear magnetic moment with a relative precision of parts‐per‐billion or better. Methods similar to those used in proton and antiproton magnetic moment measurements are applied. As those techniques rely on the challenging detection of single spin‐flips, a novel Penning trap design optimized for nuclear spin‐flip detection is developed. Abstract : A new experiment for the first direct measurement of the 3 He 2+ nuclear magnetic moment with parts per billion (ppb) precision is being constructed. For this purpose a new Penning trap optimized for nuclear spin‐flip detection is developed.